Predicting how altering propagule pressure changes establishment rates of biological invaders across species pools. Issue 3 (1st March 2014) - Brockerhoff, Eckehard G.; Kimberley, Mark; Liebhold, Andrew M.; Haack, Robert A.; Cavey, Joseph F.
Abstract : Biological invasions resulting from international trade can cause major environmental and economic impacts. Propagule pressure is perhaps the most important factor influencing establishment, although actual arrival rates of species are rarely recorded. Furthermore, the pool of potential invaders includes many species that vary in their arrival rate and establishment potential. Therefore, we stress that it is essential to consider the size and composition of species pools arriving from source regions when estimating probabilities of establishment and effects of pathway infestation rates. To address this, we developed a novel framework and modeling approach to enable prediction of future establishments in relation to changes in arrival rate across entire species pools. We utilized 13 828 border interception records from the United States and New Zealand for 444 true bark beetle (Scolytinae) and longhorned beetle (Cerambycidae) species detected between 1949 and 2008 as proxies for arrival rates to model the relationship between arrival and establishment rates. Nonlinearity in this relationship implies that measures intended to reduce the unintended transport of potential invaders (such as phytosanitary treatments) must be highly effective in order to substantially reduce the rate of future invasions, particularly if trade volumes continue to increase.